Phospholipidome profile of and metadata associated with the abdomen muscle of female Northern shrimp Pandalus borealis collected in the wild from four geographic origins in the Northwest Atlantic - Feugere, Lauric; Fernandes, Joana Filipa; Guscelli, Ella; Melo, Tânia; Aveiro, Susana; Chabot, Denis; Calado, Ricardo; Domingues, Rosário; Madeira, Diana; Calosi, Piero (PANGAEA, 2025)
The dataset contains information on the phospholipidome profile of the abdomen muscle of female Northern shrimp Pandalus borealis collected in the wild from four geographic origins in the Northwest Atlantic: St. Lawrence Estuary (SLE; 48° 35' N, 68° 35' W, May 2018; Event "SLE_Pandalus_2018"), Eastern Scotian Shelf (ESS; 45° 23' N, 61° 04' W, February 2019; Event "ESS_Pandalus_2019"), Esquiman Channel (EC; 50° 44' N, 57°29' W, July 2019; Event "EC_Pandalus_2019") and Northeast Newfoundland Coast (NNC; 50° 18' N, 54° 16' W, November 2019, Event "NNC_Pandalus_2019"). Female shrimp were exposed for 30 days under laboratory conditions to several ocean global change scenarios, with three temperatures (low temperature of 2 °C, intermediate temperature of 6 °C, and elevated temperature of 10 °C) and pH (current pH 7.75 and low pH 7.40). This experiment aimed to determine the changes in the phospholipidome profiles of shrimp from different origins in response to different scenarios of future ocean global changes combining Ocean Warming (OW) and Ocean Acidification (OA) and low dissolved oxygen (DO). Phospholipid species were quantified in abdomen muscle of female shrimp using high-resolution HILIC-MS/MS. Several datasets are provided, containing (i) the raw data expressed as peak area, (ii) the peak area data recalibrated to the internal standards for each class of phospholipid, and (iii) the final normalised data following transformation using ordered quantile normalisation, along with (iv) the metadata associated with abdomen muscle samples. A total of 269 phospholipids were identified and quantified from 260 female shrimp, with 10 shrimp per treatment sampled from two tanks per treatment (5 shrimp in each). Phospholipid peak areas were determined using Xcalibur data system v3.3 (Thermo Fisher Scientific, USA). Shrimp that molted/died during respirometry experiments were excluded from the analysis. Shrimp that were exposed to low DO were removed from the dataset prior to data transformation and downstream statistical analysis, but the raw data is provided.
Keywords: Acclimatization; adaptation; crustacean; global change; lipidomics; multipopulations; multi-stressors; Pandalus borealis; stress